The impacts of capital structure on firm’s operational efficiency - Nguyễn, Thị Quỳnh Thi ([s.l.], 2020)
This thesis consists 4 chapters: Chapter I: Literature Review and Theoretical Framework of Capital Structure and Operational Efficiency. Chapter II: Data and Research Methodology. Chapter III: Results and Experimental Discussion. Chapter IV: Conclusions and Recommendations